Gaining and losing imperial favour in late antiquity : representation and reality - Choda, Kamil; Leeuw, Maurits Sterk de,; Schulz, Fabian, (Impact of Empire;, 2020)
The collective volume Gaining and Losing Imperial Favour in Late Antiquity: Representation and Reality, edited by Kamil Cyprian Choda, Maurits Sterk de Leeuw and Fabian Schulz, offers new insights into the political culture of the Roman Empire in the 4th and 5th centuries A.D., where the emperor's favour was paramount. The articles examine how people gained, maintained, or lost imperial favour. The contributors approach this theme by studying processes of interpersonal infl uence and competition through the lens of modern sociological models. Taking into account both political reality and literary representation, this volume will have much to offer students of late-antique history and/or literature as well as those interested in the politics of pre-modern monarchical states.